Sistem Pertahanan pada Kawasan Desa Bali Aga di Kabupaten Karangasem - Swanendri, Ni Made; Suryada, I Gusti Agung Bagus (Jurnal Arsitektur Lansekap; Vol.9, No.2, Oktober 2023DO - 10.24843/JAL.2023.v09.i02.p15, 2023)
Defense System in the Bali Aga Village Area in Karangasem Regency. The defense system is one of the important things in settlements. Oscar Newman has developed the concept of defensible space, which is a defense concept to improve the quality of residential environments. The Bali Aga people still carry out their traditions, both in terms of customs and in living. Many of the characteristics of the Bali Aga settlements are still clearly visible, because the traditional concepts are still adhered to by most of the people. Aspects of the concept of defense in Bali Aga settlements have not been disclosed much. The disclosure of the concept of defense in the Bali Aga settlement is expected to add references to improve the quality of settlements. This research was conducted in three Bali Aga settlements, namely Timbrah Village, Asak Village, and Bungaya Village, in Karangasem Regency. This village was chosen because it has a location that is close together and has many similarities, in terms of customs and geographical conditions. This research uses a qualitative approach. Data collection was carried out by means of literature studies, observations, and in-depth interviews. Descriptive data were analyzed by content analysis. The results of the study show that the concept related to the defense system in living is seen in spatial organizations that emphasize the occurrence of natural surveillance. The concept of defense is also in the form of establishing boundaries in the yard of the house, and limiting access. Communal space is the center of the area, emphasizing the concept of openness to facilitate control over the behavior of the community and outsiders.